Development Of Polyurethane/Clay Nanocomposites Based On Palm Oil Polyol - Rihayat, Teuku (2008)

(untitled)
Polyurethanes (PURs) are very versatile polymeric materials with a wide range of physical and chemical properties. PURs have desirable properties such as high abrasion resistance, tear strength, shock absorption, flexibility and elasticity. Although they have relatively poor thermal stability, this can be improved by using treated clay. Polyurethane/clay nanocomposites have been synthesized from renewable sources. A polyol for the production of polyurethane by reaction with an isocyanate was obtained by the synthesis of palm oil-based oleic acid with glycerol. Dodecylbenzene sulfonic acid (DBSA) was used as catalyst and emulsifier. The unmodified clay (kunipia-F) was treated with cetyltrimethyl ammonium bromide (CTAB-mont) and octadodecylamine (ODA-mont). The d-spacing in CTAB-mont and ODA-mont were 1.571 nm and 1.798 nm respectively and larger than that of the pure-mont (1.142 nm). The organoclay was completely intercalated in the polyurethane, as confirmed by a wide angle x-ray diffraction (WAXD) pattern. Polyurethane/clay nanocomposites were prepared by a pre-polymer method and were evaluated by fourier transform infrared (FTIR) spectra to determine micro-domain structures of segmented PU, CTAB-mont-PU 1, 3, 5 wt% and ODA-mont-PU 1, 3, 5 wt%. The morphology of the nanocomposites was characterized by X-ray diffraction (XRD) and the pattern showed that all of the nanocomposites produced from this work are of the intercalated type. These were further confirmed by transmission electron microscopy (TEM) observation and scanning electron microscopy (SEM) when the surfaces of the materials were studied. Thermal stability was investigated with thermogravimetric analysis (TGA). The results showed that adding clay demonstrated better thermal stability in comparison with the virgin polyurethane. Onset degradation of pure PU is at 200 o C, and is lower than that of the CTAB-mont PU and ODA-mont PU which takes place at about 318 o C and 330 o C, respectively. The mechanical properties (including the dynamic mechanical properties) of pure polyurethane (PU) and PU/clay nanocomposites, were measured. The modified organoclay had a remarkably beneficial effect on the strength and elongation at break of the nanocomposites, which both increased with increasing clay content with the increase of the tensile strength of more than 214% and 267% by the addition of only 5 wt% of the montmorillonite CTAB-mont PU and ODA-mont PU, respectively.